Transparent polycarbonate material capable of being carved by laser and preparation method of transparent polycarbonate material
By adding the radiac feed mother grains to the radial auxiliary agent to the transparent polycarbonate material, the problem of strong laser penetration during laser laser carvings is solved, and the effect of high light light and high -precision laser carving is achieved. Engineering field.
Patent Information
- Application Number
- CN202411685301.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-28
AI Technical Summary
When laser engraving is performed on conventional transparent materials, the laser is prone to direct penetration, resulting in low engraving accuracy, poor effect, and the addition of complex components affects the optical transparency of the material.
The radiac feed mother grains made of polycarbonate, antioxidants, lubricants, and radium carved aids (mixtures composed of inorganic salts and metal oxides) are mixed together. A transparent polycarbonate material for laser laser carving.
The high light and high machining performance of the material can be realized. While maintaining good transparency, it can achieve high -precision laser radium carving effects, avoiding the negative effects of complex components on transparency.
Smart Images

Figure CN119371802A_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a transparent polycarbonate material capable of being laser engraved and a preparation method thereof, belonging to the technical field of polymer materials. Background Art
[0002] Polycarbonate (PC) is a type of amorphous engineering plastic with excellent comprehensive performance. It not only has high electrical insulation and flame retardancy, but also has excellent mechanical properties, high heat deformation temperature, UV resistance, aging resistance, and good mechanical properties within normal use temperature. Among general engineering plastics, polycarbonate has higher transparency than other materials, with a light transmittance of 85% to 90%. It is mainly used in the fields of high transparency and high impact strength. As an optical material for optical discs, it is one of the main uses of polycarbonate. In terms of electronic and electrical products, polycarbonate and its alloys can be used in the housings of household appliances, general communication equipment, and lighting equipment.
[0003] Laser marking is a technology that uses high-energy-density lasers to partially irradiate workpieces, vaporize the surface material or cause a chemical reaction that changes color through thermal effects, thereby leaving a permanent mark. Compared with traditional electrochemical, mechanical and other marking methods, laser marking has the advantages of no pollution, high speed, high quality, great flexibility, and no contact with the work surface. In recent years, laser laser engraving has replaced traditional marking methods and become a conventional processing method. Laser laser engraving includes two methods: hot processing and cold processing; "hot processing" has a laser beam with a high energy density irradiating the surface of the material being processed. The surface of the material absorbs the laser energy and generates a thermal excitation process in the irradiated area, thereby causing the surface of the material to undergo metamorphosis, melting, ablation, evaporation and other phenomena; "cold processing" has photons with very high load energy, which can break the chemical bonds in the material or the surrounding medium, causing the material to undergo non-thermal process damage.
[0004] There are certain limitations in laser engraving on conventional transparent materials. The laser can easily penetrate directly, but the transparent material cannot absorb the energy of the laser, resulting in low engraving precision and poor effect. The patent with application number CN200710176404.6, "A laser-markable resin composition and its preparation method", discloses a resin composition comprising acrylonitrile-butadiene-styrene copolymer, polycarbonate and acrylate powder rubber, which forms a dark mark under laser irradiation to improve the clarity and contrast of the mark. The patent with application number CN201510880395.3, "A high-strength polycarbonate composite capable of laser marking and its preparation method", discloses a composite comprising polycarbonate resin, glass fiber, silicon copolymer polycarbonate, compatibilizer, acetic acid copolymer and various additives to maintain high strength and high finish. In summary, the prior art often achieves the problems of ensuring the performance of the material after laser marking and low marking precision by modifying the matrix resin or adding various complex components, but the overly complex addition of components and the modification of the matrix resin will affect the optical transparency of the material. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a transparent polycarbonate material capable of being laser engraved and a preparation method thereof. The prepared material can always maintain high light transmittance and is suitable for high-precision laser engraving operations.
[0006] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:
[0007] The present invention provides a laser-able transparent polycarbonate material, comprising the following components by weight percentage:
[0008] Polycarbonate 97-99.4%;
[0009] Antioxidant 0.2-0.5%;
[0010] Lubricant 0.2-0.5%;
[0011] Laser engraving masterbatch 0.2-2%;
[0012] The laser carving masterbatch is formed by melt-blending polycarbonate, antioxidant, lubricant and laser carving auxiliary agent and then granulating; the laser carving auxiliary agent is a mixture of inorganic salt and metal oxide; the average particle size of the laser carving auxiliary agent is less than 100nm.
[0013] Furthermore, the amount of polycarbonate added to the laser carving masterbatch accounts for 94.2% of the total weight of the laser carving masterbatch, the amount of antioxidant added accounts for 0.5% of the total weight of the laser carving masterbatch; the amount of lubricant added accounts for 0.3% of the total weight of the laser carving masterbatch, and the amount of laser carving additive added accounts for 5% of the total weight of the laser carving masterbatch.
[0014] Furthermore, the polycarbonate is synthesized by phosgene method, and has a weight average molecular weight of 2.4-3.2W.
[0015] Furthermore, the antioxidant is one or a mixture of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylphenyl) phosphite, and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite.
[0016] Furthermore, the lubricant is one or a mixture of paraffin, silane polymer, fatty acid salt, fatty acid amide, methylene bisstearic acid amide, N,N-ethylene bisstearic acid amide, pentaerythritol stearate.
[0017] Furthermore, the inorganic salt in the laser engraving auxiliary agent is at least one of potassium phosphate, sodium phosphate and zinc sulfate.
[0018] Furthermore, the metal oxide in the laser engraving auxiliary agent is at least one of zinc oxide, titanium dioxide, manganese dioxide, tin dioxide, bismuth oxide, copper oxide, molybdenum oxide, nickel oxide or a composite crystal thereof.
[0019] The present invention also provides a method for preparing a transparent polycarbonate material capable of laser engraving, comprising the following steps:
[0020] (1) Add polycarbonate, laser engraving additive, antioxidant and lubricant according to preset weight percentage into a high-speed mixer and mix thoroughly;
[0021] (2) feeding the mixture into a twin-screw extruder through a metering feeding device for melt blending, and extruding and granulating to obtain laser engraving masterbatch;
[0022] (3) adding polycarbonate, laser engraving masterbatch, antioxidant and lubricant according to a preset weight percentage into a high-speed mixer, mixing them evenly, and then feeding them into a twin-screw extruder for melt blending;
[0023] (4) Extruding, drawing, cooling, slicing, and drying the mixture that is fully melt-blended and extruded to obtain a transparent polycarbonate material that can be laser engraved.
[0024] Furthermore, the melt extrusion temperature is 220-250° C., the screw length-to-diameter ratio of the twin-screw extruder is (40-44):1, and the screw speed is 300-350 rpm.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The transparent polycarbonate material capable of laser engraving provided by the present invention has simple components, avoids the complicated addition of components in the prior art, reduces the impurity content in the material, and helps to ensure the light transmittance of the polycarbonate material; the prepared transparent polycarbonate material has high light transmittance, high weather resistance and high processing performance, and can be widely used in various optical and engineering fields;
[0027] 2. In the prior art, pure polycarbonate material has high transparency, but the laser beam used in laser engraving will directly penetrate the material layer and cannot effectively form the laser engraving effect. The present invention adds a laser engraving auxiliary agent composed of metal oxides and inorganic salts. The mutual matching of inorganic salts and metal oxides provides diffusivity, increases the metal oxide's absorption of laser, and achieves good light transmittance by adding a small amount of metal oxide. Secondly, the particle size distribution of the laser engraving auxiliary agent is small, and the amount of laser engraving auxiliary agent added is small, which can allow light to pass through and achieve visual transparency. At the same time, it can promote the absorption of laser to a certain extent, so that the surface of the transparent polycarbonate material can form a laser engraving effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are the laser engraving effect diagrams of the transparent polycarbonate materials of Examples 1, 3, 4 of the present invention and the comparative example. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with preferred embodiments and the accompanying drawings. The endpoints of the ranges disclosed in the present invention and any values are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be deemed to be specifically disclosed herein.
[0030] The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources; Example 1
[0031] The transparent polycarbonate material capable of laser engraving in this embodiment includes the following components by weight percentage:
[0032] Polycarbonate 99.1%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol (antioxidant AT-76) 0.2%, tris(2,4-di-tert-butylphenyl) phosphite (antioxidant AT-168) 0.3%, lubricant 0.3% and laser engraving masterbatch 0.2%; the lubricant in this embodiment can be Lonza PETS;
[0033] The laser carving masterbatch is made of polycarbonate, antioxidant, lubricant and laser carving auxiliary agent by melt blending and granulation; the addition amount of polycarbonate accounts for 94.2% of the total weight of the laser carving masterbatch, and the addition amount of antioxidant accounts for 0.5% of the total weight of the laser carving masterbatch; the addition amount of lubricant accounts for 0.3% of the total weight of the laser carving masterbatch, and the addition amount of laser carving auxiliary agent accounts for 5% of the total weight of the laser carving masterbatch; the antioxidant in this embodiment includes antioxidant AT-76 and antioxidant AT-168, the addition amount of antioxidant AT-76 accounts for 0.2% of the total weight of the laser carving masterbatch, and the addition amount of antioxidant AT-168 accounts for 0.3% of the total weight of the laser carving masterbatch;
[0034] The laser engraving agent is a mixture of inorganic salts and metal oxides; the average particle size of the laser engraving agent is less than 100 nm. In this embodiment, the inorganic salt constituting the laser engraving agent is zinc sulfate, and the metal oxide is a composite crystal of bismuth oxide, molybdenum oxide and titanium dioxide.
[0035] Among them, polycarbonate is synthesized by phosgene method; polycarbonate synthesized by phosgene method is obtained by condensation polymerization in the presence of sodium hydroxide using bisphenol A and phosgene as raw materials, dichloromethane as solvent, and phenol as molecular weight regulator. The weight average molecular weight of the polycarbonate used in this embodiment is 2.4-3.2W; the polycarbonate synthesized by phosgene method is polycarbonate resin 2100, which is a medium viscosity resin. In addition to polycarbonate resin 2100, the polycarbonate in the present invention can also be at least one of aliphatic polycarbonate, aromatic polycarbonate, and aliphatic-aromatic polycarbonate.
[0036] Example 2
[0037] The difference between Example 2 and Example 1 is that the transparent polycarbonate material capable of laser engraving comprises the following components in percentage by weight:
[0038] Polycarbonate 98.9%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol (antioxidant AT-76) 0.2%, tris(2,4-di-tert-butylphenyl) phosphite (antioxidant TA-168) 0.3%, lubricant 0.3% and laser carving masterbatch 0.4%.
[0039] Example 3
[0040] The difference between Example 3 and Example 1 is that the transparent polycarbonate material capable of laser engraving comprises the following components in percentage by weight:
[0041] Polycarbonate 98.7%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol (antioxidant AT-76) 0.2%, tris(2,4-di-tert-butylphenyl) phosphite (antioxidant AT-168) 0.3%, lubricant 0.3% and laser carving masterbatch 0.6%.
[0042] Example 4
[0043] The difference between Example 4 and Example 1 is that the transparent polycarbonate material capable of laser engraving comprises the following components in percentage by weight:
[0044] Polycarbonate 98.3%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol (antioxidant AT-76) 0.2%, tris(2,4-di-tert-butylphenyl) phosphite (antioxidant AT-168) 0.3%, lubricant 0.3% and laser carving masterbatch 1.0%.
[0045] Example 5
[0046] The difference between Example 5 and Example 1 is that the transparent polycarbonate material capable of laser engraving comprises the following components in percentage by weight:
[0047] Polycarbonate 97.3%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol (antioxidant AT-76) 0.2%, tris(2,4-di-tert-butylphenyl) phosphite (antioxidant AT-168) 0.3%, lubricant 0.3% and laser carving masterbatch 2.0%.
[0048] Comparative Example 1
[0049] The transparent polycarbonate material capable of laser engraving in this comparative example comprises the following components in percentage by weight:
[0050] Polycarbonate 99.3%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol (antioxidant AT-76) 0.2%, tris(2,4-di-tert-butylphenyl) phosphite (antioxidant AT-168) 0.3% and lubricant 0.3%; compared with the above-mentioned embodiment of the present invention, no laser engraving masterbatch is added in the comparative example.
[0051] In summary, the specific formulations of the above Examples 1-5 and Comparative Example 1 are shown in Table 1 below:
[0052] Table 1
[0053] Comparative Example Example 1 Example 2 Example 3 Example 4 Example 5 PC 2100 99.3 99.1 98.9 98.7 98.3 97.3 Laser engraving masterbatch 0 0.2 0.4 0.6 1 2 Antioxidant AT-76 0.2 0.2 0.2 0.2 0.2 0.2 Antioxidant AT-168 0.3 0.3 0.3 0.3 0.3 0.3 Lubricant PETS 0.2 0.2 0.2 0.2 0.2 0.2
[0054] The components in the above-mentioned Examples 1 to 5 and Comparative Example 1 are used to prepare a transparent polycarbonate material capable of laser engraving, comprising the following steps:
[0055] Firstly, prepare laser engraving masterbatch;
[0056] (1) Add polycarbonate, laser engraving additive, antioxidant and lubricant according to preset weight percentage into a high-speed mixer and mix thoroughly;
[0057] (2) feeding the mixture into a twin-screw extruder through a metering feeding device for melt blending, and extruding and granulating to obtain laser engraving masterbatch;
[0058] Granulate again to prepare transparent polycarbonate material that can be laser engraved:
[0059] (3) adding polycarbonate, the prepared laser engraving masterbatch, antioxidant, and lubricant according to a preset weight percentage into a high-speed mixer, mixing them thoroughly and evenly, and then feeding them into a twin-screw extruder for melt blending;
[0060] (4) Extruding, drawing, cooling, slicing, and drying the mixture that is fully melt-blended and extruded to obtain a transparent polycarbonate material that can be laser engraved.
[0061] The melt extrusion temperature of the laser engraving masterbatch and the transparent carbonate material obtained by the double granulation is 220-250°C, the screw length-diameter ratio of the twin-screw extruder is (40-44):1, and the screw speed is 300-350rpm.
[0062] The transparent polycarbonate materials prepared in Examples 1 to 5 and Comparative Example 1 were tested for relevant performance indicators under the same test conditions. The test results are shown in Table 2 below:
[0063] Table 2
[0064]
[0065] In the above Table 2, the test methods for each performance index are as follows:
[0066] The tensile strength was tested according to ISO 527 standard with a tensile speed of 50 mm / min;
[0067] The bending strength was tested according to ISO 178 standard with a bending rate of 2 mm / min;
[0068] Notched impact strength is tested according to ISO 180 standard, and the notch type is type A;
[0069] The transmittance is tested according to ASTM D1003 standard with a thickness of 2mm;
[0070] The laser engraving effect is achieved by making a color plate and using a YAG laser marker to perform surface laser engraving test and comparison.
[0071] The performance test results of Examples 1 to 5 and the comparative example in Table 2 show that: after the laser engraving masterbatch composed of inorganic salts and metal oxides is used as an auxiliary agent in the present invention, the good comprehensive performance of the prepared transparent polycarbonate material is not changed, and the tensile strength, bending strength and notched impact strength are still maintained. The transmittance is still above 90%, which proves that the laser engraving masterbatch added in the present invention does not affect the transmittance of the transparent material; and after the transparent polycarbonate samples of the comparative example and Examples 1 to 5 are subjected to laser surface laser engraving tests, from Figure 1 It can be clearly seen that compared with the fact that normal transparent materials such as comparative example 1 cannot be laser marked, the samples of the present invention after adding laser masterbatch can achieve laser marking, and the marking is basically clear. When the concentration of laser masterbatch is higher, the transmittance decreases.
[0072] The following Examples 6-10 describe various examples of different components and weight percentages of the transparent polycarbonate material capable of laser engraving:
[0073] Example 6
[0074] The transparent polycarbonate material capable of laser engraving in this embodiment includes the following components by weight percentage:
[0075] Polycarbonate 99.1%, triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] 0.2%, bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite 0.3%, lubricant 0.3% and laser engraving masterbatch 0.2%; the lubricant in this embodiment can be a mixture of paraffin wax and silane polymer;
[0076] The laser carving masterbatch is made by melt blending polycarbonate, antioxidant, lubricant and laser carving auxiliary agent and then granulating; the amount of polycarbonate added accounts for 94.2% of the total weight of the laser carving masterbatch, the amount of antioxidant added accounts for 0.5% of the total weight of the laser carving masterbatch; the amount of lubricant added accounts for 0.3% of the total weight of the laser carving masterbatch, and the amount of laser carving auxiliary agent added accounts for 5% of the total weight of the laser carving masterbatch; the antioxidant in this embodiment includes triethylene glycol di[β-(3-tert-butyl -4-hydroxy-5-methylphenyl) propionate] and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, wherein the addition amount of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] accounts for 0.2% of the total weight of the laser carving masterbatch, and the addition amount of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] accounts for 0.3% of the total weight of the laser carving masterbatch;
[0077] The laser engraving agent is a mixture of inorganic salts and metal oxides; the average particle size of the laser engraving agent is less than 100 nm. In this embodiment, the inorganic salt constituting the laser engraving agent is zinc sulfate, and the metal oxide is a composite crystal of bismuth oxide, molybdenum oxide and titanium dioxide.
[0078] Example 7
[0079] The difference between Example 7 and Example 6 is that the transparent polycarbonate material capable of laser engraving comprises the following components by weight percentage:
[0080] Polycarbonate 99.1%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol 0.2%, tris(2,4-di-tert-butylphenyl) phosphite 0.3%, lubricant 0.3% and laser carving masterbatch 0.2%; in this embodiment, the lubricant is a mixture of methylene bisstearic acid amide and N,N-ethylene bisstearic acid amide;
[0081] The laser carving masterbatch is formed by melt-blending polycarbonate, antioxidant, lubricant and laser carving auxiliary agent and then granulating; the laser carving auxiliary agent is a mixture of inorganic salt and metal oxide; the average particle size of the laser carving auxiliary agent is less than 100nm. In this embodiment, the inorganic salt constituting the laser carving auxiliary agent is potassium phosphate, and the metal oxide is a composite crystal of zinc oxide, nickel oxide and tin dioxide.
[0082] Example 8
[0083] The difference between Example 8 and Example 6 is that the transparent polycarbonate material capable of laser engraving comprises the following components by weight percentage:
[0084] Polycarbonate 99.1%, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.2%, tris(2,4-di-tert-butylphenyl) phosphite 0.3%, lubricant 0.3% and laser carving masterbatch 0.2%; in this embodiment, the lubricant is a mixture of pentaerythritol stearate and silane polymer.
[0085] The laser carving masterbatch is formed by melt-blending polycarbonate, antioxidant, lubricant and laser carving auxiliary agent and then granulating; the laser carving auxiliary agent is a mixture of inorganic salt and metal oxide; the average particle size of the laser carving auxiliary agent is less than 100nm. In this embodiment, the inorganic salt constituting the laser carving auxiliary agent is sodium phosphate, and the metal oxide is a composite crystal of copper oxide, molybdenum oxide and manganese dioxide.
[0086] The above embodiments prove that the changes in the composition and content within the scope defined by the present invention can enable the final transparent polycarbonate material to maintain good tensile strength, bending strength and notched impact strength, and the transmittance is still maintained at more than 90%, and laser marking can be achieved, and the marking is basically clear.
[0087] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A laser-able transparent polycarbonate material, characterized in that: The composition comprises the following components by weight percentage: Polycarbonate 97-99.4%; Antioxidant 0.2-0.5%; Lubricant 0.2-0.5%; Laser engraving masterbatch 0.2-2%; The laser carving masterbatch is formed by melt-blending polycarbonate, antioxidant, lubricant and laser carving auxiliary agent and then granulating; the laser carving auxiliary agent is a mixture of inorganic salt and metal oxide; the average particle size of the laser carving auxiliary agent is less than 100nm.
2. The transparent polycarbonate material capable of laser engraving according to claim 1, characterized in that: The amount of polycarbonate added to the laser carving masterbatch accounts for 94.2% of the total weight of the laser carving masterbatch, the amount of antioxidant added accounts for 0.5% of the total weight of the laser carving masterbatch; the amount of lubricant added accounts for 0.3% of the total weight of the laser carving masterbatch, and the amount of laser carving auxiliary agent added accounts for 5% of the total weight of the laser carving masterbatch.
3. The transparent polycarbonate material capable of laser engraving according to claim 1, characterized in that: The polycarbonate is synthesized by phosgene method, and has a weight average molecular weight of 2.4-3.2W.
4. The laser-able transparent polycarbonate material according to claim 1, characterized in that: The antioxidant is one or a mixture of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, tris(2,4-di-tert-butylphenyl) phosphite, and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite.
5. The laser-able transparent polycarbonate material according to claim 1, characterized in that: The lubricant is one or a mixture of paraffin, silane polymer, fatty acid salt, fatty acid amide, methylene bis stearic acid amide, N,N-ethylene bis stearic acid amide, pentaerythritol stearate.
6. The laser-able transparent polycarbonate material according to claim 1, characterized in that: The inorganic salt in the laser engraving auxiliary agent is at least one of potassium phosphate, sodium phosphate and zinc sulfate.
7. The laser-able transparent polycarbonate material according to claim 1, characterized in that: The metal oxide in the laser engraving auxiliary agent is at least one of zinc oxide, titanium dioxide, manganese dioxide, tin dioxide, bismuth oxide, copper oxide, molybdenum oxide, nickel oxide or a composite crystal thereof.
8. A method for preparing a transparent polycarbonate material capable of laser engraving according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Add polycarbonate, laser engraving additive, antioxidant and lubricant according to preset weight percentage into a high-speed mixer and mix thoroughly; (2) feeding the mixture into a twin-screw extruder through a metering feeding device for melt blending, and extruding and granulating to obtain laser engraving masterbatch; (3) adding polycarbonate, laser engraving masterbatch, antioxidant and lubricant according to a preset weight percentage into a high-speed mixer, mixing them evenly, and then feeding them into a twin-screw extruder for melt blending; (4) Extruding, drawing, cooling, slicing, and drying the mixture that is fully melt-blended and extruded to obtain a transparent polycarbonate material that can be laser engraved.
9. The method for preparing a transparent polycarbonate material capable of laser engraving according to claim 8, characterized in that: The melt extrusion temperature is 220-250° C., the screw length-diameter ratio of the twin-screw extruder is (40-44):1, and the screw speed is 300-350 rpm.
Citation Information
Patent Citations
Laser marked resin composite and preparation method thereof
CN101418110B
High strength polycarbonate composite capable of marking through laser
CN105400168A